Nature of Reduced States in Titanium Dioxide as Monitored by Electron Paramagnetic Resonance. II: Rutile and Brookite Cases - Livraghi, Stefano; Rolando, Manuela; Maurelli, Sara; Chiesa, Mario; Paganini, Maria Cristina; Giamello, Elio (Journal of physical chemistry. C, 2014)
We have systematically used electron paramagnetic resonance (EPR) to understand the nature of excess electron centers in titanium dioxide and to classify their spectroscopic features. Excess electrons in TiO2 (probably the most important photoactive oxide) have been generated either by photoinduced charge separation or by reductive treatments and are stabilized in the solid by titanium ions which reduce to paramagnetic Ti3+. These are monitored by EPR and classified on the basis of their g tensor values in order to amend a certain confusion present in the literature about this subject. In the previous paper of this series (S. Livraghi et al. J. Phys. Chem. C 2011, 115, 25413–25421), excess electron centers in anatase were investigated while the present one is devoted to rutile and brookite, the two other TiO2 polymorphs, in the aim of providing a thorough and consistent guideline to researchers working in the wide area of titanium dioxide applications.